2013
DOI: 10.1159/000356595
|View full text |Cite
|
Sign up to set email alerts
|

ART1 Silencing Enhances Apoptosis of Mouse CT26 Cells via the PI3K/Akt/NF-κB Pathway

Abstract: Background/Aims: Colorectal carcinoma is one of the most common cancers world-wide, with high morbidity and mortality rates. Arginine ADP-ribosyltransferase 1(ART1) is an important ecto-ADP-ribose transferase and has been proven to be intimately involved in a number of biological processes. However, the influence of ART1 on survival and apoptosis of colorectal carcinoma cells and the potential mechanism of action of ART1 remain uncharacterized. Methods: ART1 was silenced via lentiviral vector-mediated short ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…A previous study (11) has shown that ART1 expression was increased in colorectal cancer and has a positive correlation with the expression of vascular endothelial growth factor (VEGF), which suggests that it may have an association with tumor angiogenesis. It has also been observed that the silencing of ART1 in CT26 cells may inhibit the proliferation of cells by restraining cell cycle at the G0/G1 phase, suppressing matrix adhesion and migration in vitro (12–14). However, whether the changes of ART1 in CT26 cells are able to affect the proliferation and invasion in vivo has yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (11) has shown that ART1 expression was increased in colorectal cancer and has a positive correlation with the expression of vascular endothelial growth factor (VEGF), which suggests that it may have an association with tumor angiogenesis. It has also been observed that the silencing of ART1 in CT26 cells may inhibit the proliferation of cells by restraining cell cycle at the G0/G1 phase, suppressing matrix adhesion and migration in vitro (12–14). However, whether the changes of ART1 in CT26 cells are able to affect the proliferation and invasion in vivo has yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Bcl-2, which is a target of NF-κB, is involved in protection from apoptosis [22]. It has been demonstrated that some agents can activate NF-κB and stimulate Bcl-2 gene promoter activity in the MIA-PaCa-2 human pancreatic cancer cell line [23].…”
Section: Discussionmentioning
confidence: 99%
“…These substrate proteins are involved in cell proliferation, angio- genesis, and inflammation (Zolkiewska and Moss 1995;Jones and Baird 1997;Saxty et al 2001;Paone et al 2002). Moreover, the ART1 expression has been reported to be upregulated in human colorectal carcinoma and hepatocellular carcinoma, and silencing ART1 in CT26 colon adenocarcinoma cells can significantly inhibit cell proliferation and promote cell apoptosis Xiao et al 2013;Su et al 2014). The functions of ART1 may include various pathways including the ERK and AKT signaling, as well as the integrin and poly (ADP-ribose) polymerase (PARP-1) signaling Xiao et al 2013Xiao et al , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the ART1 expression has been reported to be upregulated in human colorectal carcinoma and hepatocellular carcinoma, and silencing ART1 in CT26 colon adenocarcinoma cells can significantly inhibit cell proliferation and promote cell apoptosis Xiao et al 2013;Su et al 2014). The functions of ART1 may include various pathways including the ERK and AKT signaling, as well as the integrin and poly (ADP-ribose) polymerase (PARP-1) signaling Xiao et al 2013Xiao et al , 2015. In our studies, RT-qPCR analysis indicated that the mRNA expression level of ART1 in glioma was higher than that in normal brain tissues, and we found that the positive expression of ART1 was closely correlated with highergrade of glioma and can serve as an independent predictor for the poorer prognosis of glioma patients.…”
Section: Discussionmentioning
confidence: 99%